Relationship between Lithuanian sovereign credit risk and equity market - Abazoriūtė, Aistė; Kregždė, Arvydas (Business, Management and Economics Engineering, 2015)
We analyse relationship between Lithuanian sovereign credit risk and equity market. The aim of the paper is to find the impact of the sovereign credit risk, which is expressed in the terms of Credit Default Swaps (CDS), on the movements of stocks prices of Lithuania. We use VAR (vector autoregression) model in order to find the relationship between Lithuanian CDS spread and OMX Vilnius index. We use impulse reaction method to investigate the impact of CDS spreads on the OMX Vilnius index. After analysis of equity index OMX Vilnius and Lithuanian CDS price relationship it was found out that there exists an opposite relationship between these two variables. When the CDS prices are rising, the equity prices decrease and vice versa. The main finding is that Lithuanian capital market returns reacts immediately to the changes of credit risk of Lithuania which is set by the global capital market and expressed by the CDS prices and Lithuanian capital market is under the great foreign pressure.